Research Productivity of Chinese Young Thousand Talents - Yang, Lili; Marini, Giulio (International Higher Education, 2019)
While it is commonly agreed that globally bred talent returning to China greatly contributes to the enhancement of research capacity, whether returnees perform better than those who stay overseas remains to be examined. We compared the research productivity of Chinese “Young Thousand Talents” (Y1000Ts) and Chinese researchers remaining in the United States. The results of our analysis demonstrate that while the two groups publish at a similar rate, Y1000T lag slightly behind their US-affiliated counterparts in terms of quality of publications. This could be explained by the assessment system of research performance in China.